2001
DOI: 10.2134/jeq2001.3041438x
|View full text |Cite
|
Sign up to set email alerts
|

Spatio–Temporal Patterns of Soil Phosphorus Enrichment in Everglades Water Conservation Area 2A

Abstract: The Florida Everglades have undergone significant ecological change resulting from anthropogenic manipulation of historical regimes of hydrology, nutrient loading, and fire. Water Conservation Area 2A (WCA-2A) in the northern Everglades has been a focal point for the study of ecological effects of nutrient loading, especially phosphorus (P), from the nearby Everglades Agricultural Area (EAA). The overall objective of our study was to evaluate recent (1990 to 1998) changes in the spatial extent and patterns of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 27 publications
3
87
1
Order By: Relevance
“…In WCA-3 from 1992 to 2003, we estimated that the area with TPm >500 mg kg −1 increased at a rate of approximately 1% year −1 . While this represented a considerably high rate of increase, it was still lower than a rate of 5.25% year −1 calculated for WCA-2A from 1991 to 1998 (DeBusk et al, 2001). Our data indicated that while nutrient loading to WCA-3 has affected a smaller percentage of the area of WCA-3 than WCA-2A, the total area of WCA-3 with TPm > 500 mg kg −1 in both 1992 and 2003 was greater than the total area of WCA-2A with TPm > 500 mg kg −1 in 1998.…”
Section: Geostatistical Analysescontrasting
confidence: 57%
“…In WCA-3 from 1992 to 2003, we estimated that the area with TPm >500 mg kg −1 increased at a rate of approximately 1% year −1 . While this represented a considerably high rate of increase, it was still lower than a rate of 5.25% year −1 calculated for WCA-2A from 1991 to 1998 (DeBusk et al, 2001). Our data indicated that while nutrient loading to WCA-3 has affected a smaller percentage of the area of WCA-3 than WCA-2A, the total area of WCA-3 with TPm > 500 mg kg −1 in both 1992 and 2003 was greater than the total area of WCA-2A with TPm > 500 mg kg −1 in 1998.…”
Section: Geostatistical Analysescontrasting
confidence: 57%
“…P loading from precipitation is difficult to accurately determine but is estimated to be 14.7 Mg P/yr (Davis 1994). Eutrophication has resulted in a large expanse of enriched soil that has significantly influenced the vegetation composition (Davis 1994, DeBusk et al 2001, Sklar et al 2005. This area has also been well studied in terms of ecological structure and function (Appendix).…”
Section: Study Sitementioning
confidence: 99%
“…However, the maximum TP values in the hotspots from 1992 were in the 450 to 550 mg kg 21 range, rather than the 620 to 720 mg kg 21 range reported in this study. Historical background TP concentrations in WCA-2A have been estimated to be less than 500 mg kg 21 (DeBusk et al, 2001). Adopting this estimate for WCA-3, according to our interpolated map, 25% (179 ha) of 3AN currently has elevated TP levels.…”
mentioning
confidence: 95%